The Dominant Factors of Physical Environmental Conditions That Affect The Incidence of Malaria (Study in The Village of Tuafanu, South-Central Timor, East Nusa Tenggara) - Reza Fitri Yanti; Mindiharto, Sestiono; Budiono, Nugrahadi Dwi Pasca; Inayah, Zufra (Yayasan Ahmad Mansyur Nasirah, 2024)
Malaria is an infectious disease caused by Plasmodium sp parasites that grow and multiply in human erythrocytes. The incidence of malaria consists of three epidemiological components: agent, host and environmental factors. Risk factors that contribute greatly to the occurrence of malaria are the environmental conditions where humans and mosquitoes live. This research aims to analyze the dominant factors of physical environmental conditions that influence the incidence of malaria in Tuafanu Village, South Central Timor, NTT. The research was conducted with an analytic observational approach with a Case-Control Study approach. The number of samples was 60 samples with a ratio of 1:1, namely 30 cases and 30 controls taken based on purposive sampling technique. Data were collected using secondary data from BBTKLPP Surabaya in 2023. Statistical analysis used chi square test and logistic regression test. There was a significant relationship between house floor, house wall, ceiling and puddle around the house with malaria incidence in Tuafanu Village because the P-value <0.05. In all households, there was no wire mesh in the ventilation of the house. Based on the analysis of the dominant factor of physical environmental conditions that affect malaria in Tuafanu Village is puddles with a p-value of 0.012 and an OR of 0.091, which means that individuals who live in the area around their house there are puddles or stagnant water are 0.091 higher risk of malaria. The OR value < 1 indicates that puddles act as a protective factor against malaria, therefore it is necessary to clean and manage the environment to prevent the presence of water that can become a breeding place for mosquitoes and prevent malaria transmission.